Exploring Social and Environmental Accounting Reporting Through Jurgen Habermas's Critical Theory - Yahya; Amrizal Salida; Nurul Rusdiansyah (West Science Interdisciplinary Studies, 2023)
The objective of this research is to uncover how accounting practices related to social and environmental aspects in the Bakaru hydropower plant are carried out. The informants in this study consisted of employees and local communities around the company. They have a good understanding of the issues under study. Data is collected through observation and recording of documentation in various situations in the field. The collected data were analyzed using a qualitative approach using the theory of critical communicative action from Jürgen Habermas. This approach is used to examine the real practice of social and environmental accounting. The results showed that the Corporate Social Responsibility (CSR) program at the Bakaru hydropower plant is in line with the view of how natural relationships should be carried out, in accordance with the concept of truth proposed by Jurgen Habermas. That is, companies are responsible for the impact of their operations, and this is based on the expectations of various interested parties. The company has also achieved a level of compliance in this regard, by implementing CSR through disclosure to the public. However, there is a problem in the budget allocation for CSR programs every year, because the implementation of these programs does not run effectively. In this case, the Bakaru hydropower plant does not fully meet claims of authenticity or honesty, and most of the programs carried out are still assistance and do not have a focus on sustainability in terms of reporting, prevention, and maintenance of environmental activities.